2008
DOI: 10.1038/cr.2008.69
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II promotes NO production, inhibits apoptosis and enhances adhesion potential of bone marrow-derived endothelial progenitor cells

Abstract: Abbreviations: endothelial progenitor cells (EPCs); endothelial cells (ECs); mononuclear cells (MNCs); angiotensin II (AngII); angiotensin II type 1 receptor (AT1R); renin-angiotensin system (RAS); nitric oxide (NO); bone marrow (BM); peripheral blood (PB); vascular endothelial growth factor (VEGF); basic fibroblast growth factor (bFGF); vascular endothelial growth factor receptor-2 (VEGFR-2); 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT); endothelial nitric oxide synthase (eNOS); angioten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 33 publications
1
37
1
Order By: Relevance
“…Rat bone marrow-derived MNCs were isolated by density gradient centrifugation with Ficoll, as previously described (Yin et al 2008). MNCs were seeded on fibronectin-coated plates at a density of 10 6 cells per cm 2 in EGM-2MV (Lonza, Verviers/B, Endothelial cell basal medium-2, plus FBS, VEGF, R 3 -IGF-1, rhEGF, rhFGF-B, GA-1000, hydrocortisone and ascorbic acid).…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rat bone marrow-derived MNCs were isolated by density gradient centrifugation with Ficoll, as previously described (Yin et al 2008). MNCs were seeded on fibronectin-coated plates at a density of 10 6 cells per cm 2 in EGM-2MV (Lonza, Verviers/B, Endothelial cell basal medium-2, plus FBS, VEGF, R 3 -IGF-1, rhEGF, rhFGF-B, GA-1000, hydrocortisone and ascorbic acid).…”
Section: Animalsmentioning
confidence: 99%
“…Cell proliferation EPC proliferative capacity was measured using the 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assay as previously described (Yin et al 2008). After serum starvation for 24 h, cells were treated with PIN (1.25-200 mg/L, Sigma) dissolved in DMSO or pretreated with PI3-kinase inhibitor (LY294002) or NOS inhibitor (L-NAME) before treatment with PIN.…”
Section: Measuring the Biological Functions Of Epcsmentioning
confidence: 99%
“…In vitro studies have shown that eNOS/NO signaling enhance the mobilization, homing, and adhesion of EPCs (35,36). eNOS/NO signaling is associated with BPD (13).…”
Section: Lung Enos and Vegf Were Increased When Combining Epcs Transpmentioning
confidence: 99%
“…The more acute stimulatory effects in cultured EPCs depend on AT 1 R-mediated facilitation of vascular endothelial growth factor-mediated NO release, involving an increased vascular endothelial growth factor receptor and endothelial NO synthase expression, as well as antiapoptotic phosphatidylinositol 3/Akt signaling. 2,7 The chronic, deleterious effects on cultured EPCs depend on ROS release, and accumulation of damage to macromolecules, in particular to DNA, might be a necessary, timeconsuming interlude between ROS release and induction of …”
mentioning
confidence: 99%
“…This is in sharp contrast with the antiapoptotic, proangiogenic effect of Ang II on EPCs that was observed in other studies. 2,7,8 These stimulatory effects of Ang II takes place on a shorter term (Յ5 days). Therefore, the paradoxical findings seem to be based on a temporal difference in exposure to Ang II.…”
mentioning
confidence: 99%